2020
DOI: 10.1002/joc.6814
|View full text |Cite
|
Sign up to set email alerts
|

Changing spatio‐temporal trends of heat wave and severe heat wave events over India: An emerging health hazard

Abstract: Heat wave (HW) and severe heat wave (SHW) events are the manifestations of extreme temperature causing an array of impacts on health, ecosystem, and economy. Since the mid-20th century, an increasing trend in the characteristics of heat waves has been observed over India causing an increased rate in human mortality. Our study aimed to analyse monthly, seasonal, and decadal variations along with long-term trends of HW and SHW events for premonsoon (March-May) and early summer monsoon (June-July) season during 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…For example, storm events channel pesticides from fields into aquatic environments in the form of pulses. Also, ultraviolet-B (UV-B) radiation is an intrinsically pulsed stressor due to its dial nature and dependence on cloud cover. Heat waves may further increase the risk of occurrence and intensity of those pulsed stressors, which can occur in any arbitrary order or temporal alignment in nature.…”
Section: Introductionmentioning
confidence: 99%
“…For example, storm events channel pesticides from fields into aquatic environments in the form of pulses. Also, ultraviolet-B (UV-B) radiation is an intrinsically pulsed stressor due to its dial nature and dependence on cloud cover. Heat waves may further increase the risk of occurrence and intensity of those pulsed stressors, which can occur in any arbitrary order or temporal alignment in nature.…”
Section: Introductionmentioning
confidence: 99%
“…So far the research on heat and cold waves is concerned, most of them focused on the identification of HW and CW events of some specific years, and trends (Mahdi and Dhekale, 2016;Chakraborty et al, 2019;Das et al, 2020;Singh et al, 2021;, their mechanisms of formation (Ratnam et al, 2016) and fatalities (Malik et al, 2020). All these works reported that the north western and central parts of India are experienced heat waveprone areas and Jammu & Kashmir as well as north western parts and some portions of Central India are cold waves prone areas in their respective period of study.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [56] used mean land surface temperature to map heat wave hazard in China. Similarly, Wu et al [47] argue the mean temperature level across 24 h during a heat wave predicts mortality and morbidity rates better than maximum and minimum temperatures; yet, most studies focus on maximum daytime or nighttime temperature as an indicator of heat wave hazard [71][72][73].…”
Section: Introductionmentioning
confidence: 99%